Geochemical and clay mineralogical characteristics of the Woodford Shale, Payne County, Oklahoma - Alkhammali, Sultan A. (Kansas State University, 2015)
Chemical and mineralogical compositions of < 2 µm-size fraction clays of the shale source rocks of Devonian-Mississippian age in northern Oklahoma were determined to find any link between the minerals and the generation of petroleum. Ten samples of clay separates were analyzed for their mineral composition, major element contents, K/Rb ratios, and REE contents. XRD analyses and SEM showed the presence of discrete illite, the most dominant clay mineral, with smaller amounts of mixed-layer illite/smectite, chlorite, and kaolinite. The non-clay minerals found in the Woodford Shale from this study include quartz, dolomite, calcite, pyrite, feldspar (albite and microcline), and apatite. The clays in these rocks have a range of K/Rb ratios between 160 and 207. These ratios are considerably lower than the ratios of average silicate minerals (clays), with expected ratios between 250 and 350. It could be that clays received K and Rb from a solution, which was partly involved in oil generation by which oil received more K relative to Rb making the aqueous phase depleted in K/Rb ratios (Alvarez, 2015). Thus, the low K/Rb ratios for these clays may be reflecting signatures of reactions involving oil generation. The total REE contents ranged between 13 and 30 ppm. The low total REE contents of < 2 µm-size fraction clays in the Woodford Shale as compared to average sedimentary rocks which may be represented by values given either PAAS 184 ppm or NASC with 178 ppm, may suggest that the formation of the clays was linked to oil generation, having known of the face from the study of Alvarez (2015) that crude oils could have higher specific REE concentrations than the associated formation waters. PAAS-normalized REE patterns for these samples display positive Gd anomalies. Two out of the ten samples had prominent Ce anomalies. Only three out of ten samples had Eu positive anomalies, one of which was quite prominent. All samples had MREE enrichment, superimposed on either a flat REE distribution patterns with enrichment in LREE. Only one pattern showed the distribution with a distinct HREE enrichment. The MREE anomalies could be from the effect of phosphate mineralization. In fact, the X-ray diffraction patterns of random powder samples showed the presence of fluorapatite and chlorapatite in most of the studied samples. The total organic carbon (TOC) contents of the whole rocks ranged from 0.5 to 6.54 wt.%. Thus, it can be concluded that hydrocarbon generation potential of the Woodford shale (0.8-4.44 wt.%) is significantly higher than Mississippian Lime unit (0.5 wt.%). Only one sample, which belonged to pre-Woodford Shale Hunton group, had the highest value of TOC. The available K-Ar dates of < 2 µm-size fraction clays suggest that the clays are authigenic (illites) for at least some samples. The dates ranged from 318.6 ± 7.9 Ma (Serpukhovian) to 353.9 ± 7.9 Ma (Tournaisian). All dates are younger than the times of deposition of the Woodford Shale. Assuming there is a genetic link between formation of authigenic illite and hydrocarbon generation, this study suggests that oil generation may have taken place on an average about 30 Ma after the deposition of the Woodford Shale.
Keywords: Geology; Geology (0372)